The Efforts of the Cimahi Police Traffic Turjawali Unit in Overcoming the Congestion of the Lembang Line on Holidays - Iqbal Putra Saimuri (Advances in Police Science Research Journal, 2021)
This research is motivated by the occurrence of congestion on the Lembang route on holidays. In order to overcome the recurring congestion, it is necessary to know how the efforts made by the Turjawali unit in overcoming congestion on the Lembang route on holidays, the causes of congestion on the Lembang route and the factors that affect the efforts of the Turjawali Unit in overcoming congestion. This study uses several concepts and theories in discussing the problem, these concepts are the concept of effort, the concept of congestion, the concept of smooth traffic, and the concept of traffic engineering. While the theory used is SWOT analysis theory, traffic engineering theory and management theory (6M). This research was conducted with a qualitative approach, with descriptive analysis methods, as well as data collection techniques by interview, observation, and document review. Techniques in analyzing the data used were data reduction, data presentation and drawing conclusions. The results of the study found that the efforts made by the Turjawali Unit in overcoming congestion on the Lembang route on holidays were considered not optimal. The things that cause congestion are the number of vehicles passing on the Lembang lane, road conditions and factors from humans themselves. As well as the factors that influence the efforts of the Cimahi Police Traffic Turjawali Unit are the lack of available facilities and infrastructure and the lack of expert members who can be empowered, as well as road equipment that has started to become unfit for use is an inhibiting factor. Meanwhile, the supporting factor is the presence of members who are able to work together, competent leaders and good coordination. Based on the results of the research, the efforts made by the Turjawali Unit were to open and close routes, regulate, implement anticipatory strategies and mobilize members quickly. The suggestions put forward are adding members and implementing vocational education, preferably collaborating with the Community Service Unit or Kamsel Unit to conduct community service to the community, and proposing suggestions for collaborating with related agencies to improve APIL and markers.